Disruption of Saccadic Adaptation with Repetitive Transcranial Magnetic Stimulation of the Posterior Cerebellum in Humans - Jenkinson, Ned (Springer-Verlag, 2010)
Saccadic eye movements are driven by motor commands that are continuously modified so that errors created by eye muscle fatigue, injury, or—in humans—wearing spectacles can be corrected. It is possible to rapidly adapt saccades in the laboratory by introducing a discrepancy between the intended and actual saccadic target. Neurophysiological and lesion studies in the non-human primate as well as neuroimaging and patient studies in humans have demonstrated that the oculomotor vermis (lobules VI and VII of the posterior cerebellum) is critical for saccadic adaptation. We studied the effect of transiently disrupting the function of posterior cerebellum with repetitive transcranial magnetic stimulation (rTMS) on the ability of healthy human subjects to adapt saccadic eye movements. rTMS significantly impaired the adaptation of the amplitude of saccades, without modulating saccadic amplitude or variability in baseline conditions. Moreover, increasing the intensity of rTMS produced a larger impairment in the ability to adapt saccadic size. These results provide direct evidence for the role of the posterior cerebellum in man and further evidence that TMS can modulate cerebellar function.